Numerical analysis to estimate near-wellbore drilling induced failures area for fractured formation using Universal Discrete Element Codes (UDEC). Issue 1 (1st January 2021) - Rwechungula, James C; Cheng, Yuanfang
Abstract: There have been reported cases of wellbore instability near-wellbore area due to failures associated with drilling operations, the magnitude and extension of the failure area is imprecisely evaluated by copious researchers due to some of the limitations posed by the numerical simulations used. Therefore, this paper estimates a failure zone area near-wellbore based on the conducted coupled Thermal-Hydro Mechanical (THM) analysis integrated into UDEC, wellbore enlargement, and Failure area analysis. A two-dimensional horizontal plane stress model of 2 × 2 m is created using rock properties from a vertical well, and a wellbore radius of 0.11 m is drilled under confined stress using the in-situ stresses. The Voronoi tessellation joint system was used to create randomly polygon fractures referred to as Discrete Fracture Size (DFS). The coding of various parameters was performed to study the near-wellbore stability for both underbalanced and overbalanced drilling conditions, the four cases of DFS were used against seven wellbore pressures. After comparing with other DFS, The parametric analysis at DFS of 0.1 and 0.12 m offers low shear and block displacements that led to an induced shear and tensile failures, respectively. However, to evaluate the optimal DFS, a comparison is done using Failure area and Borehole enlargement analysis, and the results show that DFS of 0.12 m yields significantly low wellbore enlargement rate and failure area zone for all stress ratios and drilling cases. The proposed simple model for wellbore failure area estimations is verified against a well vertical section located in Northern China.